When Grandma Gatewood took a hike - Houts, Michelle (Ohio University Press, 2016)
In 1955, sixty-seven-year-old Emma "Grandma" Gatewood became the first woman to solo hike the entire length of the Appalachian Trail in one through hike. Michelle Houts and Erica Magnus bring us the first children's book about her feat and the unexpected challenges she encountered on the journey she initially called a "lark."